2019
DOI: 10.22146/mot.45762
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Citrus Sinensis Peel Extract Against Isoniazid and Rifampicin-induced Liver Injury in Wistar Rats

Abstract: Tuberculosis (TB) is one of the leading causes of death in developing countries. One of the problems in controlling TB disease is that most anti-tuberculosis drugs are hepatotoxic. Citrus sinensis peel extract is the rich source of secondary metabolites with high potential effectiveness as an antioxidant. In the present study, we evaluate the hepatoprotective effect of Citrus sinensis peel ethanolic extract (CSPEE) on isoniazid and rifampicin-induced liver injury in Wistar rats. Twenty five adult male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Moreover, this complex will influence the gene expression of the cell. Kuhnle et al reported that orange peels contented 36 µg/100g wet weight of phytoesterogen based on the LC-MS 13 and C-Labelled standard. 18 Moreover, Shalaby et al reported that the presence of flavanones, flavones, and flavonols in Citrus sinensis and Citrus aurantifolia leaf or peel showed a powerful estrogen-like activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this complex will influence the gene expression of the cell. Kuhnle et al reported that orange peels contented 36 µg/100g wet weight of phytoesterogen based on the LC-MS 13 and C-Labelled standard. 18 Moreover, Shalaby et al reported that the presence of flavanones, flavones, and flavonols in Citrus sinensis and Citrus aurantifolia leaf or peel showed a powerful estrogen-like activity.…”
Section: Discussionmentioning
confidence: 99%
“…The filtered remaceration and maceration were evaporated by rotary evaporator at a temperature of 70 o C and then followed by concentrated using the oven at 40 o C until they become thick extracts. 12,13 After that, the ethanol extract of Sunkist peels was suspended into the sodium carboxymethylcellulose to form oral suspension. The oral suspension used 0.5% Sodium Carboxymethyl cellulose as vehiculum.…”
Section: Methodsmentioning
confidence: 99%
“…After 3 days, it was filtered by filter paper, and then the residue was re-macerated with 600 ml of 96% ethanol for 3 days. The filtered remaceration and maceration were evaporated by rotary evaporator at a temperature of 70°C and then followed by concentrated using the oven at 40°C until they become thick extracts [12], [13].…”
Section: Methodsmentioning
confidence: 99%
“…was re-macerated with 600 ml of 70% ethanol for 3 days. The filtered maceration and maceration were evaporated by rotary evaporator at a temperature of 70°C and then followed by concentrated using the oven at 40 o C until they become thick extracts [11,12].…”
Section: Mutia and Suhartinamentioning
confidence: 99%